2000
DOI: 10.1116/1.1323970
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of sputtered and spin-coatable aluminum oxide electron beam resists

Abstract: Articles you may be interested inSpin-coatable Hf O 2 resist for optical and electron beam lithographies J. Vac. Sci. Technol. B 28, 90 (2010); 10.1116/1.3273536 Polysubstituted derivatives of triphenylene as high resolution electron beam resists for nanolithography J.Control of the structure and properties of aluminum oxide coatings deposited by pulsed magnetron sputtering J. Vac. Sci. Technol. A 17, 945 (1999); 10.1116/1.581669 Magnetic nanostructures produced by electron beam patterning of direct write t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Amorphous Al 2 O 3 is sputtered primarily via volume dissociated mechanisms exhibiting rapid and abrupt mass-loss, attributed to the displacement of metallic Al and the formation of oxygen gas bubbles due to anion aggregation. [143], [144] This mechanism explains the rapid pore [133,143] The decreased yet constant expansion rate observed in stage III of figure 21b is consistent with this result. Mochel et al also reported steady, constant growth rates during the formation of nanometer sized holes in metal β-aluminas.…”
Section: Nanopore Expansion Kineticssupporting
confidence: 84%
“…Amorphous Al 2 O 3 is sputtered primarily via volume dissociated mechanisms exhibiting rapid and abrupt mass-loss, attributed to the displacement of metallic Al and the formation of oxygen gas bubbles due to anion aggregation. [143], [144] This mechanism explains the rapid pore [133,143] The decreased yet constant expansion rate observed in stage III of figure 21b is consistent with this result. Mochel et al also reported steady, constant growth rates during the formation of nanometer sized holes in metal β-aluminas.…”
Section: Nanopore Expansion Kineticssupporting
confidence: 84%
“…Amorphous Al 2 O 3 is sputtered primarily via volume dissociated mechanisms exhibiting rapid and abrupt mass-loss, attributed to the displacement of metallic Al and the formation of oxygen gas bubbles due to anion aggregation. [21], [22] This mechanism explains the rapid pore expansion initially observed (stage II of Figure 2b). With continued electron beam irradiation, the amorphous Al 2 O 3 support transitions into a hybrid polycrystalline-metallic structure (O to Al ratio of ~0.6).…”
Section: Resultsmentioning
confidence: 93%
“…Under e-beam exposure, the naphthenate molecules are cross-linked, increasing the molecular weight of the resist, making it insoluble in the developer. In comparison to sputtered materials, the sensitivity seems to increase by almost a factor of 10 6 when resists are spin coated and if their structure is chemically changed [52,53]. For example, the spin-coatable Al 2 O 3 resists show an e-beam sensitivity of approximately 50 mC cm −2 , whereas for the sputtered Al 2 O 3 resist the electron dose is about 5 × 10 6 mC cm −2 .…”
Section: Inorganic Resistsmentioning
confidence: 99%
“…Compared with the sputtered metal oxide resists, under e-beam irradiation the spin coated resists seem to need only a few bonds to be broken (low dose) in order to make the irradiated area insoluble in the developer solution. Ten-nm isolated resist lines and 15 nm lines etched into silicon were obtained with a spin-coatable 60 nm thick Al 2 O 3 resist layer [52]. The exposure was performed in a modified Hitachi HL-700F ebeam exposure system at 70 keV.…”
Section: Inorganic Resistsmentioning
confidence: 99%